Dental modifications: a perspective of Indonesian chronology and the current applications - Rusyad Adi Suriyanto; Toetik Koesbardiati (Dental Journal (Majalah Kedokteran Gigi), 2010)
Background: Dental modifications are one of the forms of initiation rite. Thus tradition can be found in all of Indonesian regions, even in South East Asia, in previous era. Modes and dentistry, as a culture product, including its modifications or decorations toward body and teeth have appeared in present day, such as tattoo and decorations on teeth which are taken particular model and superimpose or inculcate ornament of jewel, diamond, gold and others. The first research aim is to describe how functions of modifications on teeth represent cultural affinity and population of biologic affinity that accompany it from time to time; starting from prehistoric period to present day, especially in Indonesian region. The second aim is to submit applicable proposal that is useful for medical area, particularly in dentistry. Method: The research materials include teeth of the adult human skulls of Java, Balinese, and East Nusa Tenggara from some paleoanthropological–archaeological sites, as well as isolated permanent dental sample from modern Balinese population. The methods used are visual comparative descriptive method, and browsed through ethnographic and archaeological classic literatures. Result: Chronologically, dental modifications as reference to the pattern of migration and the domination of the culture in the past, and these facts indicate to the biological affinity and indicate to how the culture influences other culture. Conclusion: Some effects of the practices of dental modifications are the emergence of some diseases. Therefore, it is necessary for the agent of health and the traditional practitioner to be aware when they practice the dental modifications. Nevertheless, on the other side, based on explanations the research results, it is clear that dental modifications provide broader knowledge, because it has a very long journey of migration history, occupancy, and culture in this Indonesian Archipelago, which stretches from the period of about ten thousand years ago until now. This knowledge can be used for either practical purposes of medicine and dentistry even forensic. Thus, it is also useful in forensic identification, as guidance with cultural background such as certain patterns of dental modifications cannot be disregarded. In the same way, patterns of modifications either intentional or unintentional can give a guidance to strengthen identification.Latar belakang: Modifikasi gigi geligi adalah salah satu bentuk ritus inisiasi. Tradisi ini dapat ditemukan di seluruh wilayah Indonesia, bahkan di Asia Tenggara pada masa lalu. Persoalan-persoalan kecantikan dan dentistri sebagai produk budaya termasuk modifikasi dan dekorasi tubuh dan gigi geligi telah muncul pada masa kini, contohnya tatto tubuh atau dekorasi gigi geligi dengan ornament hiasan dari emas, intan berlian dan juga bahan lainnya. Tujuan awal dari penelitian ini adalah untuk mendeskripsikan bagaimana fungsi modifikasi gigi geligi mewakili afinitas kultural dan afinitas biologis dari suatu populasi yang saling berkaitan dari waktu ke waktu, dimulai dari masa prasejarah hingga masa kini, terutama di wilayah Indonesia. tujuan penelitian yang kedua adalah untuk menyumbangkan pemikiran yang aplikatif yang berguna untuk bidang kesehatan terutama dentistri. Metode: Bahan penelitian adalah gigi geligi dari tengkorak dewasa Jawa, Bali dan Nusa Tenggara yang berasal dari situs-situs paleoantropologis-arkeologis, demikian pula sampel gigi geligi permanen individual dari populasi Bali saat ini/modern. Metode yang digunakan adalah deskriptif komparatif visual, dan penelusuran literatur etnografi dan arkeologi klasik. Hasil: Secara kronologis, modifikasi gigi geligi adalah rujukan bagi migrasi pada masa lalu dan dominasi budaya masa lalu. Kenyataan ini menunjukkan adanya afinitas biologis dan menunjukkan bagaimana budaya yang satu dapat mempengaruhi budaya yang lain. Simpulan: Beberapa efek dari praktek modifikasi gigi geligi adalah timbulnya beberapa penyakit. Oleh karena itu, hal ini sangat penting diketahui oleh praktisi kesehatan modern dan praktisi kesehatan tradisional untuk mempertimbangkan kenyataan ini dalam melakukan praktek modifikasi gigi geligi. Di sisi lain, berdasarkan hasil penelitian ini, modifikasi gigi geligi memberikan pengetahuan dan wawasan yang sangat luas, karena modifikasi gigi geligi telah lama dilakukan melalui perjalanan yang panjang dalam sejarah migrasi, penghunian dan budaya di kepulauan Indonesia, dengan rentang waktu sekitar 10.000 tahun yang lalu hingga saat ini. Pengetahuan tentang hal ini dapat digunakan untuk kepentingan studi kesehatan dan dentistry, bahkan forensik. Khususnya untuk identifikasi forensic, modifikasi gigi geligi adalah petunjuk latar belakang budaya seseorang, dimana pola tertentu modifikasi gigi geligi tidak dapat diabaikan. Dengan demikian, pola modifikasi gigi geligi baik sengaja (intentional) maupun yang tidak disengaja (unintentional) merupakan penguat dari identifikasi individual.